Hubungan antara Sikap dan Penerimaan Pelajar terhadap Amalan Pembelajaran atas Talian - Mohamed Aziz, Nur Fatin Ashikin; Wahab, Eta; Shamsuddin, Alina; Abdullah, Nor Hazana; Wan Ahmad, Wan Nurul Karimah (Research in Management of Technology and Business, 2020)
Online learning is the latest method used in national learning system to ensure that the national education system is moving along with other developed countries. The purpose of this study is to examine the relationship between attitudes and acceptance of students towards online learning practices. The dimensions of student attitudes that been used were attitude of students on the ease of use, attitudes towards relative advantages and attitudes towards compatibility of use. Quantitative research methods were used in this study by distributing questionnaires to students from 8 faculties in UTHM, however only 164 students responded to the survey with a response rate of 44%. The data were analyzed using the Statistical Packages for Social Science (SPSS) software. Descriptive and correlation analysis were used to answer the research questions. This study found that both attitude and acceptance of the students towards online learning is at a moderate level. In addition, there is a significant relationship between attitude and acceptance of students towards online learning practices.